Edukasi dan Implementasi Pemberian Vitamin A di Dukuh Cibangkang Desa Ragatunjung Kecamatan Paguyangan - Himatul Khoeroh; Ahmad Ridlo; Anggi Nur Hidayah; Bestri Pebri Yanti; Nunung Febrianingsih; Meliyana Meliyana; Kartika Andelira (PPNI UNIMMAN, 2024)
Vitamin A is an essential nutrient for humans, especially toddlers, because this nutrient is very important and our food consumption tends to be insufficient and still low so it must be met from the outside. In children under five due to vitamin A deficiency will increase pain and death, easily exposed to infectious diseases, such as diarrhea, pneumonia, pneumonia and finally death.This community service objective aims to educate the benefits of vitamins and implement the provision of vitamin A as a government program every February and August. Vitamin A is given directly in the toddler class along with posyandu activities.Community Service Results The results of community service show the implementation of vitamin A provision to toddlers at the Melati Posyandu in Cibangkang Hamlet, Ragatunjung Village, Paguyangan District, Brebes Regency in 2023 there will be 51 toddlers. 42 of them received high-dose red capsules, while 5 received low lecturer blue capsules and 4 others did not get them because they were not old enough.